Gene Marcial's seven commandments of stock investing - Marcial, Gene G. (FT Press, 2008)
"Gene Marcial provides iconoclastic insights into the art of successful investing while exploding the mythology of the conventional wisdom. His 7 Commandments of Stock Investing is scintillating reading for both individual and institutional investors who seek an advantage in their moneymaking endeavors."--Scott Black, President of Delphi Management Inc. and a member of the Barron's Roundtable "It is well understood that trading in the stock market is full of risks. But if you are ready to take the plunge, I guarantee that there will be a time when being familiar with Gene Marcial's 7 Commandments of Stock Investing will be extremely important. Over the years, I have followed many of the same commandments." --Carl Icahn, Chairman, Icahn Associates "This book begins with one of the wisest investment observations I've ever encountered: 'There are plenty of ways to make money in the stock market, but clinging to mainstream thinking or so-called conventional wisdom is not one of them.' The author's discussion on avoiding the diversification trap is alone worth many times the price of this book." --Bernie Schaeffer, Chairman, Schaeffer's Investment Research, Inc., www.SchaeffersResearch.com "Gene Marcial has been guiding literally millions of investors to better financial performance over his more than 30 years as a leading financial journalist. He consistently has demonstrated a rare instinct for knowing when to follow a trend and when to think like a contrarian. In today's turbulent times, his new book, 7 Commandments of Stock Investing, is essential reading for all investors and could well add precious percentage points to the performance of any who take his words to heart." --Stephen Leeb, President, Leeb Capital Management Inc. Every week, the investment world turns to Gene Marcial's BusinessWeek column. Here's why: Marcial knows how to pick winners. Apple at 15. US Steel at 19. But Marcial's track record isn't limited to just one or two picks. In fact, recent analysis reveals that he's beaten the indexes for a full decade . You can't get results like that following the "conventional wisdom"! You need to know what Gene Marcial has learned about stock investing--and this book will tell you. Marcial has distilled 35 years of experience into seven powerful, counterintuitive "commandments": rules that are simple and practical enough for every investor to profit from. Marcial reveals why diversification is not an optimal investment strategy ... why yo ...